PENINGKATAN HASIL BELAJAR BAHASA INDONESIA MELALUI METODE ROLE PLAYING PADA SISWA SEKOLAH DASAR - Fauzatul Ma’rufah Rohmanurmeta (Universitas Ahmad Dahlan, 2017)
The purpose of this study was to determine the application of the method of role playing, improved learning outcomes, and the advantages and disadvantages of the methods of role playing in elementary school. This research use desciptive qualitative approach. Subjects in the study third grade students numbering nine people. This type of research is classroom action research with data collection through testing, observation and documentation. These data analysis techniques using data analysis with interactive models, and in the activities of analysis and data collection activities using two cycles of the first cycle and the second cycle. The results showed an increase learning outcomes Indonesian teaching methods for role playing in a drama about the beauty of nature with the provisions of ≥70 value as much as 80% of students, in cooperation with the provisions ≥75 students as much as 80% and motivated students with the provisions of ≥75 value as much as 80%. Therefore, it can be seen the advantages of this model is to make learning more fun, can improve learning outcomes Indonesian, cultivate the potential of students, improve student collaboration. While the drawbacks is that it takes a long time and needed a place large enough.